Innovation – The Main Source of Sustainable Development - Pop, Viorel (Studia Universitatis Vasile Goldiș Arad, Seria Științe Economice, 2014)
Economy - is the sum of population activities and economic progress is due to the innovative ideas of individuals from that population. Competition in innovation domain is driven by the desire for financial gain. As the private economy is driven by the desire to make profit, in the same way innovation is motivated by consistent income that may occur. The applying of innovations in economy brings benefits for all, including for those who do not innovate or do not work in innovative sectors. For a country to have a competitive economy it must produce itself applied knowledge and not to wait to get, to buy innovation from outside. Consequently, the necessary conditions for innovation must be provided: access to performant education, encouraging competition by rewarding achievements, and all these can happen only in a developed society. Romania has made huge efforts after the 2nd World War to overcome the economic backwardness, the lacking element at that time being the owned technology. Later, in ’80 the deficient element, but not only in Romania, but in all European communist countries, became creativity, its lack of performance due to the lack of wisdom of the leaders of these countries - lack of wisdom due to poor education, lack of higher and university education - that would have opened their horizons for understanding economic phenomena, for relations between the economic development and social aspects etc.. Raising people’s income is possible only by increasing productivity. Always those working in the field of high technology, those having the highest qualification, have had the highest productivity and of course the highest wages. Even now those working in the innovative areas have the highest salaries. For example, those who work at Apple, IBM and Microsoft, have salaries over 100,000. Romania should also learn from the experience of other countries that have developed innovative areas, that allow sustainable development not only to the economy but also to social, and care for the natural environment.